Information Need And Information-Seeking Behaviour Of Agricultural Extension Workers In Daerah Istimewa Yogyakarta, Indonesia - Wulandari, Retno (2010)

(untitled)
One of the important factors that contribute to agricultural development is information. As such, agricultural extension workers who link agricultural agencies to the farmers must have adequate and up-to-date information about agriculture practices before they could inform, educate and train the farmers on the methods and techniques of farming. Previous studies have shown that agricultural extension workers seldom use the internet, read books, or even go to the library and university, and research institution to obtain relevant information pertaining to their work. Therefore, there is a need to determine information seeking strategies used by these agricultural extension workers in obtaining work information relevant to their professions.This study aimed to determine the types of information needed by agricultural extension workers, the sources of information used by them to obtain information and the information seeking strategies used by the agricultural extension workers. It is also tried to identify the information seeking strategy according to selected demographic variables, and to determine the factors influencing information seeking strategies used by agricultural extension workers. This study used survey design, and it was conducted in Daerah Istimewa Yogyakarta, Indonesia. The total population of the study was 338 agricultural extension workers; cluster sampling method was used to select 181 respondents as its sample. The dependent variables involved in the study include information seeking strategies (which were further categorized as passive, active and interactive strategy), while the independent variables are selected demographic variables, types of information needs and types of information sources. A structured-questionnaire was employed as the instrument for gathering data. The data were analyzed using the Statistical Package for Social Science (SPSS version 16) and Pearson Chi Square Test was used to determine the factors influencing information seeking strategies of agricultural extension workers. In general, the finding showed that agricultural extension workers needed various information related extension service, innovation and extension role. Most of the agricultural extension workers need innovation information. Besides that, most agricultural extension workers used interpersonal source in seeking information. These agricultural extension workers also used various types of strategies; there are active, passive and interactive strategies to seek the required information. Regardless of the types of information, most agricultural extension workers were found to have used active strategy by seeking agricultural information inside and outside the agency. In addition, they also utilized interactive and passive strategy for all types of information which was sought by means of direct enquiring method and seek the information inside the agency. Factors influencing information seeking strategy used by agricultural extension workers indicated that types of information need influenced the information seeking strategy used by agricultural extension workers. Print media; electronic media and scientific meeting source influenced the information seeking strategy used by agricultural extension workers for extension service information. Whereas for information related to innovation, electronic media and scientific meeting influenced information seeking strategy. For extension role information, interpersonal, print media, electronic media and scientific meeting influenced information seeking strategy. Therefore, it was suggested that further study be conducted to cover a wider geographical area such as other provinces in Indonesia with different geographical characteristics, farming system, custom and traditions. By covering wider area, a better picture of information seeking strategies used by agricultural extension workers could be obtained.